SME Risk Management Performance in China and how it can be Affected by Individual Demographic Factos of Owner/managers - SHENG, Ling (2017)
China is now ranked as the world’s second largest economy thanks to its fast GDP growth rate. SMEs, which occupy over 97.9% of companies registered in China, has contributed greatly to the rising of China. Unfortunately, due to the characteristics SMEs as well as the immature business environment of the country, Chinese SMEs are facing more risks and are more vulnerable to risks comparing with large companies and even SMEs in other developed countries. Hence, risk management, a dedicated method used to reduce risks faced by the organisation and help with the long-term survival of the business is being increasingly valued. However, few researches have studied the risk management performance in China, especially using empirical data. Also, there is a gap in existing literatures regarding the individual demographic factors of owner/managers that can affect risk management performance of SMEs. This thesis identified the relatively poor risk management performance of Chinese SMEs and discovered that owner/managers’ age, knowledge on risk, whether have previous entrepreneurial experience have significant impact on the total risk management performance of the SME they work for.